Pyramids construction

Calculus Level 3

The Pharaoh would like to cover the lateral sides of his square pyramid with the finest marble. In order to save the cost of construction, the builder tries to reduce the exposed surface area of the pyramid as much as possible.

What is the angle of inclination θ \theta (in degrees) that minimizes the exposed surface area given a constant volume of the pyramid?


The answer is 54.7356.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

5 solutions

Markus Michelmann
Oct 12, 2017

We consider the height h h of the pyramid as a varyable parameter, whereas its side length a a is fixed by the volume V = 1 3 a 2 h = const a = 3 V h V = \frac{1}{3} a^2 h = \text{const} \quad \Rightarrow \quad a = \sqrt{\frac{3 V}{h} } Pythagorean theorem yields the height h h' of the triangular area h = a 2 4 + h 2 = 3 V 4 h + h 2 h' = \sqrt{\frac{a^2}{4} + h^2} = \sqrt{\frac{3 V}{4 h} + h^2} so that the total outer area (4 triangles) results to A = 4 1 2 a h = 2 3 V 3 V 4 h 2 + h A = 4 \cdot \frac{1}{2} a h' = 2 \sqrt{3 V} \sqrt{\frac{3 V}{4 h^2} + h} In the minimum, the derivative must be zero A h = 3 V 3 V 2 h 3 + 1 3 V 4 h 2 + h = ! 0 h 3 = 3 2 V = 1 2 a 2 h h = 1 2 a θ = arctan 2 h a = arctan 2 54.7356 \begin{aligned} & & \frac{\partial A}{\partial h} &= \sqrt{3 V} \frac{- \frac{3 V}{2 h^3} + 1}{\sqrt{\frac{3 V}{4 h^2} + h} } \stackrel{!}{=} 0 \\ \Rightarrow & & h^3 &= \frac{3}{2} V = \frac{1}{2} a^2 h \\ \Rightarrow & & h &= \frac{1}{\sqrt{2}} a \\ \Rightarrow & & \theta &= \arctan \frac{2h}{a} = \arctan \sqrt{2} \approx 54.7356 \end{aligned}

1st line: V= 1/3 a^2 h

Mike Remmers - 3 years, 7 months ago

You could have just used AM-GM instead of calculus.

Sahil Jain - 3 years, 7 months ago

Great problem.

If you calculate a couple more distances after finding h = 1 2 a h = \frac{1}{\sqrt{2}}a , you discover that the faces of the pyramid are equilateral triangles. Call d d the length of the shared edges of the triangles. h = h 2 + ( 1 2 a ) 2 = 1 2 a 2 + 1 4 a 2 = 3 2 a d = h 2 + ( 1 2 a ) 2 = 3 4 a 2 + 1 4 a 2 = a \begin{aligned} h' &= \sqrt{h^2+(\frac{1}{2}a)^2} \\ &= \sqrt{\frac{1}{2}a^2 + \frac{1}{4}a^2} \\ &= \frac{\sqrt{3}}{2}a \\ d &= \sqrt{h'^2+(\frac{1}{2}a)^2} \\ &= \sqrt{\frac{3}{4}a^2 + \frac{1}{4}a^2} \\ &= a \end{aligned}

Since the triangles are equilateral, the Pharoah's pyramid is the top half of a regular octahedron . And indeed, the dihedral angle (the angle formed by two faces) of a regular octahedron is 109.471 2 109.4712^\circ , exactly double the angle asked for in this problem.

Matthew Feig - 3 years, 7 months ago

Log in to reply

Using h' = root3/2a, sub that into the interior triangle, with base 1/2a. You will discover cos theta = 1/root 3. Inverse cos yields the correct answer. (sorry for the lack of mathematical figures on my phone keyboard)

freenate 04 - 3 years, 7 months ago

Hi, why is the answer not 1/(infinity-1)? I.e have the shortest possible pyramid thus minimising the area of the sides to a value just slightly greater than the square base? What am I missing?

Nelson Bibby - 3 years, 7 months ago

Log in to reply

A pyramid with zero height has no volume. If you keep the volume constant as you decrease the height h h further and further, the base lenght a a has to growth, so that in the limit h 0 h \to 0 the base lenght (and, therefore, also the area) is infinitely large.

Markus Michelmann - 3 years, 7 months ago

Using the diagram above:

Volume V = 1 3 a 2 h V = \dfrac{1}{3}a^2h , where a = 2 h cos θ , h = h sin θ a = 2h' \cos\theta, h = h' \sin\theta \implies

V = 4 3 h 3 cos 2 θ sin θ = K h = ( 3 K 4 cos 2 θ sin θ ) 1 3 V = \dfrac{4}{3} h'^3 \cos^2\theta \sin\theta = K \implies h' = (\dfrac{3K}{4 \cos^2\theta \sin\theta})^\dfrac{1}{3} \implies

Lateral Surface Area S = 2 a h S ( θ ) = 4 h 2 cos θ = j ( sec θ ) 1 3 ( csc θ ) 2 3 S = 2 a h' \implies S(\theta) = 4 h'^2 \cos\theta = j (\sec\theta)^\dfrac{1}{3} (\csc\theta)^\dfrac{2}{3} , where j j is just a constant.

d S d θ = j 3 ( s e c θ ) 1 3 ( csc θ ) 2 3 ( tan θ 2 cot θ ) = 0 \dfrac{dS}{d\theta} = \dfrac{j}{3} (sec\theta)^\dfrac{1}{3} (\csc\theta)^\dfrac{2}{3} * (\tan\theta - 2 \cot\theta) = 0 \implies

3 sin 2 θ 2 = 0 sin θ = ± 2 3 3 \sin^2\theta - 2 = 0 \implies \sin\theta = \pm \sqrt{\dfrac{2}{3}} . choosing sin θ = 2 3 θ = 54.735 6 \sin\theta = \sqrt{\dfrac{2}{3}} \implies \theta = 54.7356^\circ

Note: The angle θ \theta is the same for any pyramid whose base is a regular n g o n n-gon .

To show that angle θ \theta is the same for any pyramid whose base is a regular n g o n n-gon .

For area of n g o n n - gon :

Let B C = x BC = x be a side of the n g o n n - gon , A C = A B = r AC = AB= r , A D = h AD = h^* , and B A D = 180 n \angle{BAD} = \dfrac{180}{n} .

x 2 = r sin ( 180 n ) r = x 2 sin ( 180 n ) h = x 2 cot ( 180 n ) A A B C = 1 4 cot ( 180 n ) x 2 \dfrac{x}{2} = r \sin(\dfrac{180}{n}) \implies r = \dfrac{x}{2 \sin(\dfrac{180}{n})} \implies h^* = \dfrac{x}{2} \cot(\dfrac{180}{n}) \implies A_{\triangle{ABC}} = \dfrac{1}{4} \cot(\dfrac{180}{n}) x^2 \implies

A n g o n = n 4 cot ( 180 n ) x 2 A_{n - gon} = \dfrac{n}{4} \cot(\dfrac{180}{n}) x^2 \implies the Volume of the pyramid V p = n 12 cot ( 180 n ) x 2 H V_{p} = \dfrac{n}{12} \cot(\dfrac{180}{n}) x^2 H

Let A C = H AC = H be the height of the pyramid, B C = h BC = h^* , and A B = h AB = h' be the slant height of the pyramid and m C B A = θ m\angle{CBA} = \theta

The lateral surface area S = n 2 x h S = \dfrac{n}{2} x h' .

h = x 2 cot ( 180 n ) = h cos ( θ ) x = 2 tan ( 180 n ) cos ( θ ) h h^* = \dfrac{x}{2} \cot(\dfrac{180}{n}) = h' \cos(\theta) \implies x = 2 \tan(\dfrac{180}{n}) \cos(\theta) h' and H = h sin ( θ ) H = h' \sin(\theta) and letting u ( n ) = tan ( 180 n ) u(n) = \tan(\dfrac{180}{n}) \implies V p = n 3 u ( n ) cos 2 ( θ ) sin ( θ ) h = K V_{p} = \dfrac{n}{3} u(n) \cos^2(\theta) \sin(\theta) h' = K and S = n u ( n ) c o s ( θ ) h 2 . S = n * u(n) cos(\theta) h'^2.

V p = n 3 u ( n ) cos 2 ( θ ) sin ( θ ) h = K h = ( 3 K n u ( n ) c o s 2 ( θ ) s i n ( θ ) ) 1 3 S ( θ ) = j ( n ) ( s e c ( θ ) ) 1 3 ( c s c ( θ ) ) 2 3 V_{p} = \dfrac{n}{3} u(n) \cos^2(\theta) \sin(\theta) h' = K \implies h' = (\dfrac{3K}{n * u(n_) cos^2(\theta) sin(\theta)})^{\dfrac{1}{3}} \implies S(\theta) = j(n) * (sec(\theta))^{\dfrac{1}{3}} (csc(\theta))^{\dfrac{2}{3}} , where j ( n ) = ( 9 k 2 n u ( n ) ) 1 3 j(n) = (9 k^2 n * u(n))^{\dfrac{1}{3}}

d S d θ = j ( n ) 3 ( s e c θ ) 1 3 ( csc θ ) 2 3 ( tan θ 2 cot θ ) = 0 \implies \dfrac{dS}{d\theta} = \dfrac{j(n)}{3} (sec\theta)^\dfrac{1}{3} (\csc\theta)^\dfrac{2}{3} * (\tan\theta - 2 \cot\theta) = 0 \implies

3 sin 2 θ 2 = 0 sin θ = ± 2 3 3 \sin^2\theta - 2 = 0 \implies \sin\theta = \pm \sqrt{\dfrac{2}{3}} . choosing sin θ = 2 3 θ = 54.735 6 \sin\theta = \sqrt{\dfrac{2}{3}} \implies \theta = \boxed{54.7356^\circ}

\therefore The measure of the desired angle θ \theta is independent of n n .

Rocco Dalto - 3 years, 7 months ago

You forgot the '2' in the first derivative line, 2*root(3V), but it does not affect the outcome.

Steve Kessell - 3 years, 7 months ago

Shouldn't you specify that we are dealing with a right pyramid?

Abraham Zhang - 2 years, 6 months ago

How do we know that all outer triangles have the same area. They share common base but not necessarily a common height.

Saakshi Porwal - 3 years, 7 months ago

Log in to reply

Yes they do. If you imagine the right triangle drawn in the picture for every face, by Pythagorean theorem the heights of the triangular faces must be the same.

Alan Fruge - 3 years, 7 months ago

Log in to reply

No, not necessarily. Nowhere in the question does it say that we are dealing with a right pyramid.

Abraham Zhang - 2 years, 6 months ago

1st line, a=cube root (3V/h) , not square root

Joe Hamilton - 3 years, 7 months ago

Log in to reply

I corrected the typo, hopefully everything else is fine.

Markus Michelmann - 3 years, 7 months ago
Arjen Vreugdenhil
Oct 23, 2017

Let b = 1 2 a b = \tfrac12a be half of the length of a side. The volume is proportional to V b 2 h . V \propto b^2h. The area is proportional to A b h b b 2 + h 2 ; A \propto bh' \propto b\sqrt{b^2+h^2}; in order to minimize the area, we might as well minimize its square, i.e. we minimize b 4 + b 2 h 2 . b^4 + b^2h^2. We wish to express this polynomial (of fourth degree) in terms of the constant V b 2 h V \propto b^2h (third degree) and the unknown t = tan θ = h / b t = \tan\theta = h/b (zeroeth degree). This must be done as follows: b 4 + b 2 h 2 V 4 / 3 ( t 4 / 3 + t 2 / 3 ) . b^4 + b^2h^2 \propto V^{4/3}(t^{-4/3} + t^{2/3}). Thus we minimize the expression t 4 / 3 + t 2 / 3 t^{-4/3} + t^{2/3} . The easiest way to do this is by setting the derivative equal to zero: 4 3 t 7 / 3 + 2 3 t 1 / 3 = 0 ; \frac{-4}3 t^{-7/3} + \frac 2 3 t^{-1/3} = 0; multiply by 3 2 t 7 / 3 \tfrac32 t^{7/3} : 2 + t 2 = 0. -2 + t^2 = 0. We find that tan θ = t = 2 \tan\theta = t = \sqrt 2 , and so θ 54.735 6 \theta \approx \boxed{54.7356^\circ} .


Alternative

Since the volume is constant, we have (with t = tan θ = h / b t = \tan\theta = h/b ) 0 = d ( b 2 h ) = 2 b h d b + b 2 d h = b 2 ( 2 t d b + d h ) , 0 = d(b^2h) = 2bh\:db + b^2\:dh = b^2(2t\:db + dh), so that d h = 2 t d b dh = -2t\:db .

To minimize the area we minimize b 4 + b 2 h 2 b^4 + b^2h^2 (see above); we set its total derivative equal to zero: 0 = d ( b 4 + b 2 h 2 ) = ( 4 b 3 + 2 b h 2 ) d b + 2 b 2 h d h = 2 b 3 [ ( 2 + t 2 ) d b + t d h ] ; 0 = d(b^4 + b^2h^2) = (4b^3+ 2bh^2)db +2b^2h\:dh = 2b^3\left[(2 + t^2)\:db + t\:dh\right]; substitute d h = 2 t d b dh = -2t\:db , we see that 0 = ( 2 + t 2 ) d b + t d h = ( 2 + t 2 2 t 2 ) d b = ( 2 t 2 ) d b , 0 = (2 + t^2)\:db + t\:dh = (2+t^2- 2t^2)db = (2-t^2)db, from which t = 2 t = \sqrt 2 .

I love your solutions. They keep the brain engaged in a way that identifying an independent variable and 'cranking the handle' does not. I didn't understand immediately what you meant by 'degree' in this problem. Perhaps 'dimension' (in the way it is used in 'dimensional analysis') would be clearer?

But a great solution and thanks for posting.

Peter Macgregor - 3 years, 7 months ago

Log in to reply

The degree of a monomial is the sum of the exponents. The degree of a polynomial is the maximum degree of its monomials. A polynomial is homogeneous is all monomials have the same degree.

Thus, b 4 + b 2 h 2 b^4 + b^2h^2 is homogeneous and of fourth degree, and b 2 h b^2h is homogeneous and of the third degree. By extending the concept, b / h = b 1 h 1 b/h = b^1h^{-1} is of zeroeth degree.

I used these concepts to arrive at the idea of taking a 4 / 3 4/3 power: ( degree four ) = A ( degree three ) 4 / 3 ( degree zero ) n . (\text{degree four}) = A\cdot (\text{degree three})^{4/3}\cdot(\text{degree zero})^n.

Arjen Vreugdenhil - 3 years, 7 months ago

Log in to reply

That's made it very clear, Thank you.

Peter Macgregor - 3 years, 7 months ago

I derived an equation for surface area in terms of theta only, then differentiated it, setting that to zero, getting tan theta = root 2; yielding the desired answer.

Garth Kroeker - 3 years, 7 months ago
Evan Nibbe
Oct 29, 2017

I wrote a python program to optimize the volume versus the top surface area using the functions 3V/a^2=h , hprime =a/cos(theta) , and SAtop=2*hprime*a .

 1
 2
 3
 4
 5
 6
 7
 8
 9
10
11
12
13
14
15
16
17
18
19
20
21
22
23
24
25
26
27
28
29
30
31
32
33
34
35
36
37
38
V=input("What is the volume: ")
V=float(V)
a_alow=(3*V)**(1/3)
h_alow=a_alow
import math
theta_alow=math.atan(h_alow/a_alow)
h_alow_prime=a_alow/math.cos(theta_alow)
SA_top_alow=2*h_alow_prime*a_alow
a_ahigh=(3*V+1)**(1/3)
h_ahigh=3*V/a_ahigh**2
theta_ahigh=math.atan(h_ahigh/a_ahigh)
h_ahigh_prime=a_ahigh/math.cos(theta_ahigh)
SA_top_ahigh=2*h_ahigh_prime*a_ahigh
while True:
   if SA_top_ahigh>SA_top_alow:
     a_ahigh=a_alow  
     h_ahigh=h_alow
     theta_ahigh=math.atan(h_ahigh/a_ahigh)
     h_ahigh_prime=a_ahigh/math.cos(theta_ahigh)
     SA_top_ahigh=2*h_ahigh_prime*a_ahigh
     a_alow=a_alow*.99
     h_alow=3*V/a_alow**2
     theta_alow=math.atan(h_alow/a_alow)
     h_alow_prime=a_alow/math.cos(theta_alow)
     SA_top_alow=2*h_alow_prime*a_alow
  else:
     a_alow=a_ahigh
     h_alow=h_ahigh
     theta_alow=math.atan(h_alow/a_alow)
     h_alow_prime=a_alow/math.cos(theta_alow)
     SA_top_alow=2*h_alow_prime*a_alow
     a_ahigh=a_ahigh*1.01
     h_ahigh=3*V/a_ahigh**2
     theta_ahigh=math.atan(h_ahigh/a_ahigh)
     h_ahigh_prime=a_ahigh/math.cos(theta_ahigh)
     SA_top_ahigh=2*h_ahigh_prime*a_ahigh
print("theta alow is: "+str(theta_alow)+", and SA top is: "+str(SA_top_alow))
print("theta ahih is: "+str(theta_ahigh)+", and SA top is: "+str(SA_top_ahigh)) 

Why not a² cover? Inverse pyramidal is just exposed by only this square fondation (only one of This lateral side exposed), no mater of angle (more than -45° dépend of budget) ... and cheapest solution for a poor Pharaon ! ;-)

CREACH ALAIN - 3 years, 7 months ago
James Wilson
Nov 9, 2017

My solution was similar to Rocco Dalto's. I'm just amazed at how close to 54 degrees the answer was, but that it wasn't actually 54 degrees. I was initially expecting a relationship to a golden angle.

Using a Golden Triangle of sides: height h = ϕ h = \sqrt{\phi} , base b = 1 b = 1 and slant height s = ϕ s = \phi , the angle made between the slant height and the base turned out to be cos 1 ( 2 1 + 5 ) \cos^{-1}(\dfrac{2}{1 + \sqrt{5}}) ~ 51.8272 9 51.82729^\circ . Although the golden angle is ~ 137.5077 6 137.50776^\circ which has nothing to do with the Golden Triangle(mine) or your triangle which has height h = ϕ h = \phi , base b = 4 ϕ 2 b = \sqrt{4 - \phi^2} and slant height s = 2. s = 2. .

Rocco Dalto - 3 years, 6 months ago

Log in to reply

I have to go for now, but I know 2 sin ( 54 ) = ϕ 2\sin(54)=\phi .

James Wilson - 3 years, 6 months ago

Log in to reply

Using a Golden Triangle of sides: height h = ϕ h = \sqrt{\phi} , base b = 1 b = 1 and slant height s = ϕ s = \phi , the angle made between the slant height and the base turned out to be cos 1 ( 2 1 + 5 ) \cos^{-1}(\dfrac{2}{1 + \sqrt{5}}) ~ 51.8272 9 51.82729^\circ . Although the golden angle is ~ 137.5077 6 137.50776^\circ which has nothing to do with the Golden Triangle(mine) or your triangle which has height h = ϕ h = \phi , base b = 4 ϕ 2 b = \sqrt{4 - \phi^2} and slant height s = 2. s = 2. .

Rocco Dalto - 3 years, 6 months ago
Rocco Dalto
Nov 5, 2017

Using the diagram above:

Volume V = 1 3 a 2 h V = \dfrac{1}{3}a^2h , where a = 2 h cos θ , h = h sin θ a = 2h' \cos\theta, h = h' \sin\theta \implies

V = 4 3 h 3 cos 2 θ sin θ = K h = ( 3 K 4 cos 2 θ sin θ ) 1 3 V = \dfrac{4}{3} h'^3 \cos^2\theta \sin\theta = K \implies h' = (\dfrac{3K}{4 \cos^2\theta \sin\theta})^\dfrac{1}{3} \implies

Lateral Surface Area S = 2 a h S ( θ ) = 4 h 2 cos θ = j ( sec θ ) 1 3 ( csc θ ) 2 3 S = 2 a h' \implies S(\theta) = 4 h'^2 \cos\theta = j (\sec\theta)^\dfrac{1}{3} (\csc\theta)^\dfrac{2}{3} , where j j is just a constant.

d S d θ = j 3 ( s e c θ ) 1 3 ( csc θ ) 2 3 ( tan θ 2 cot θ ) = 0 \dfrac{dS}{d\theta} = \dfrac{j}{3} (sec\theta)^\dfrac{1}{3} (\csc\theta)^\dfrac{2}{3} * (\tan\theta - 2 \cot\theta) = 0 \implies

3 sin 2 θ 2 = 0 sin θ = ± 2 3 3 \sin^2\theta - 2 = 0 \implies \sin\theta = \pm \sqrt{\dfrac{2}{3}} . choosing sin θ = 2 3 θ = 54.735 6 \sin\theta = \sqrt{\dfrac{2}{3}} \implies \theta = \boxed{54.7356^\circ}

Note: The angle θ \theta is the same for any pyramid whose base is a regular n g o n n-gon .

To show that angle θ \theta is the same for any pyramid whose base is a regular n g o n n-gon .

For area of n g o n n - gon :

Let B C = x BC = x be a side of the n g o n n - gon , A C = A B = r AC = AB= r , A D = h AD = h^* , and B A D = 180 n \angle{BAD} = \dfrac{180}{n} .

x 2 = r sin ( 180 n ) r = x 2 sin ( 180 n ) h = x 2 cot ( 180 n ) A A B C = 1 4 cot ( 180 n ) x 2 \dfrac{x}{2} = r \sin(\dfrac{180}{n}) \implies r = \dfrac{x}{2 \sin(\dfrac{180}{n})} \implies h^* = \dfrac{x}{2} \cot(\dfrac{180}{n}) \implies A_{\triangle{ABC}} = \dfrac{1}{4} \cot(\dfrac{180}{n}) x^2 \implies

A n g o n = n 4 cot ( 180 n ) x 2 A_{n - gon} = \dfrac{n}{4} \cot(\dfrac{180}{n}) x^2 \implies the Volume of the pyramid V p = n 12 cot ( 180 n ) x 2 H V_{p} = \dfrac{n}{12} \cot(\dfrac{180}{n}) x^2 H

Let A C = H AC = H be the height of the pyramid, B C = h BC = h^* , and A B = h AB = h' be the slant height of the pyramid and m C B A = θ m\angle{CBA} = \theta

The lateral surface area S = n 2 x h S = \dfrac{n}{2} x h' .

h = x 2 cot ( 180 n ) = h cos ( θ ) x = 2 tan ( 180 n ) cos ( θ ) h h^* = \dfrac{x}{2} \cot(\dfrac{180}{n}) = h' \cos(\theta) \implies x = 2 \tan(\dfrac{180}{n}) \cos(\theta) h' and H = h sin ( θ ) H = h' \sin(\theta) and letting u ( n ) = tan ( 180 n ) u(n) = \tan(\dfrac{180}{n}) \implies V p = n 3 u ( n ) cos 2 ( θ ) sin ( θ ) h = K V_{p} = \dfrac{n}{3} u(n) \cos^2(\theta) \sin(\theta) h' = K and S = n u ( n ) c o s ( θ ) h 2 . S = n * u(n) cos(\theta) h'^2.

V p = n 3 u ( n ) cos 2 ( θ ) sin ( θ ) h = K h = ( 3 K n u ( n ) c o s 2 ( θ ) s i n ( θ ) ) 1 3 S ( θ ) = j ( n ) ( s e c ( θ ) ) 1 3 ( c s c ( θ ) ) 2 3 V_{p} = \dfrac{n}{3} u(n) \cos^2(\theta) \sin(\theta) h' = K \implies h' = (\dfrac{3K}{n * u(n_) cos^2(\theta) sin(\theta)})^{\dfrac{1}{3}} \implies S(\theta) = j(n) * (sec(\theta))^{\dfrac{1}{3}} (csc(\theta))^{\dfrac{2}{3}} , where j ( n ) = ( 9 k 2 n u ( n ) ) 1 3 j(n) = (9 k^2 n * u(n))^{\dfrac{1}{3}}

d S d θ = j ( n ) 3 ( s e c θ ) 1 3 ( csc θ ) 2 3 ( tan θ 2 cot θ ) = 0 \implies \dfrac{dS}{d\theta} = \dfrac{j(n)}{3} (sec\theta)^\dfrac{1}{3} (\csc\theta)^\dfrac{2}{3} * (\tan\theta - 2 \cot\theta) = 0 \implies

3 sin 2 θ 2 = 0 sin θ = ± 2 3 3 \sin^2\theta - 2 = 0 \implies \sin\theta = \pm \sqrt{\dfrac{2}{3}} . choosing sin θ = 2 3 θ = 54.735 6 \sin\theta = \sqrt{\dfrac{2}{3}} \implies \theta = \boxed{54.7356^\circ}

\therefore The measure of the desired angle θ \theta is independent of n n .

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...